Exploratory Study of Pregnant Women's Motivation to Perform Triple Elimination Examination - Nila Anggraini, Feby; Handayani, Rini; Heryana, Ade; Angeliana K, Devi; Prajna Wekadigunawan, Cri Sajjana (Rifa'Institute, 2024)
Introduction: Based on data from the SIHEPI application (Hepatitis Information System and PISP) of the Grogol Petamburan Health Center, in 2022 the total number of pregnant women who were screened for triple elimination was 2394 pregnant women. From the examination, 6 pregnant women were found with the results of the reactive HIV rapid test, 2 pregnant women with reactive Syphilis rapid test (TP rapid) and 37 pregnant women with reactive HBsAg rapid test results. Objective: This study aims to explore what motivations and supports pregnant women have who are willing to do triple elimination examinations. Method: This type of research is qualitative descriptive with phenomenological design. The determination of informants is carried out by purposive sampling techniques. Result and Discussion: The results of the study found that generally pregnant women have good healthy motivation from within themselves, pregnant women get support from their husbands in the form of information support, emotional attention, assessment in the form of positive rewards, encouragement and approval and instrumental support. Conclusion: Pregnant women also get support from family, support of information and emotional attention. Only one pregnant woman received information support from health cadres and all pregnant women received information support from health workers